Intellectual Property Rights as Credit Collateral After Published The Government Regulation Number 24 Year 2022 - Hijriya, Shafira; Anggunsuri, Upita (Nagari Law Review, 2023)
The creative economy has grown rapidly in recent years. Indonesia has published Government Regulation Number 24 Year 2022 concerning Implementing Regulations for the Creative Economy, which is expected to be able to realize the hopes of many entrepreneurs in the creative economy to gain access bank credit based on intellectual property. Bank credit guarantees are based on intellectual property and are a breakthrough in creative economy industry, but these regulations give rise to complex problems because the assets being guaranteed, namely intellectual property rights, are intangible assets, so there are concerns that banks will not accept them as credit providers. In addition, the time period for intellectual property protection is limited and there is no organization in place to evaluate intellectual property assets in Indonesia that can be used as credit collateral. The problem approach method used is the empirical juridical method. This research discusses financing based on intellectual property rights schemes and the obstacles or challenges faced by the banking industry with this financing based on intellectual property rights. The implementation on Creative Economy Government Regulation still has many obstacles in its implementation. It can be seen from many things have not been regulated clearly and in detail, for example regarding the form of Intellectual Property Rights credit collateral binding have not been clearly regulated, Intellectual Property Rights valuation mechanism and the appraisal team, execution techniques, secondary market is not available to facilitate execution. The lack of clear regulations has resulted in concerns from banking institutions about channeling credit to the creative economy because it is considered to be high risk.